Penentuan Strategi Bersaing Menggunakan Analisis SWOT (Studi Kasus Pada PT. Keong Nusantara Abadi Natar Lampung Selatan) - Herlina Putri Wulandari; Emy Khikmawati; Taminto Taminto (Universitas Malahayati, 2017)
Companies engaged in food and beverage processing is a company that can not beseparated from the problem of market competition. Therefore we need appropriate strategies toaddress the competition problems so that they can attract the attention of consumers, strengthen itsposition in the market, and withstand the pressures of competition. The first step in determining thecompetitive strategy is to make a list of questionnaires and distributing questionnaires to employees ofPT. Keong Nusantara Abadi followed by testing the questionnaire with validity and reliability testingand further by analyzing strengths, weaknesses, opportunities, and threats through a SWOT analysis.The results showed that PT. Keong Nusantara Abadi has several factors that affect the strength,weaknesses, opportunities and threats. Where the company's position is in progressive positions orpositions that indicate a strong organization and opportunity. In other words the organization in goodshape so it is possible to continue to expand, enlarge growth and achieve maximum progress. Thecompany has had the right strategy but still have to fix some of the weaknesses of the company and toavoid or defend against the threat of companies that have better service with by developing theexisting strategy